Discussion of The Eyeballs Have It: Searching for the Value in Internet Stocks - Keating, Elizabeth K. (Journal of Accounting Research, 2000)
Research on the valuation of firms is a new and important area of accounting research. There are widespread claims that stocks in the high-tech sector were overpriced in the late 1990s. Research in this area could assess this contention as well as the magnitude and nature of any mispricing. Moreover, accountants are interested in the effectiveness of the accounting system in capturing firm value. New Economy firms are of particular interest because of concerns about whether the traditional accounting model can be used to value firms in instances where most of that value consists of growth opportunities. The Trueman, Wong, and Zhang (henceforth TWZ) paper contributes to our understanding of valuation by studying the Internet sector. Internet firms are characterized by rapid growth, high degrees of innovation, and reliance on intangible assets, such as patents, software, marketing and promotions, brand name, reputation, customer satisfaction, and knowledge management. TWZ investigate the role of accounting and Internet use data in valuing Internet firms, carefully avoiding inferences about absolute under- or overvaluation. The authors use a residual income valuation model and incorporate two eyeball measures of web activity, unique visitors and pageviews. Of the accounting measures they test, gross profits but not earnings are